Defensive strategy and critical match episodes in basketball game: analysing the teams` success - Ferreira, A. P.; Didier, S.; Volossovitch, A. (World Congress of Performance Analysis of Sport IX, 2012)
Tactical variability is an essence of teams¡¦ sports competition (Garganta, 2009). The so-called Critical Match Episodes (CME) can be a consequence of these tactical changes, when one team tries to overlap its opponent. This study aimed to investigate the defensive strategies of basketball teams in the CME comparing them with the Normal Match Episodes (NME), when teams achieved different levels of match success. The current score of 80 matches from the Basketball Portuguese League were reconstructed by ball possession. Each match was analysed according to the model of coach¡¦s game practical knowledge (Ferreira et al., 2010). A CME was considered as a transition of the equilibrium match state. A NME was defined as an episode, in which the match remained in the same equilibrium state. A total of 319 CME and 318 NME were determined. The NME were randomly selected respecting a homogeneity criterion with the CME identified in each match. Defensive strategy was analysed in each ball possession during the CME and NME. Seven main categories were considered to analyse the teams¡¦ defensive performance: (1) Global Strategy to the Defensive Transition (GSDT), (2) Defensive Pressure to the Outlet (DPO), (3) Ball Pressure in Defensive Transition (BPDT); (4) Defensive Phase (DP); (5) Defensive Type (DT); (6) Opposition Level to the Field Goals (OLFG) and (7) the Ball Recovering (BR). A total of 2665 ball possessions from CME and 2671 from NME were observed; intra and inter-observer ratings, estimated using the K-Cohen test, were 0,78-0,85. Teams were classified according to the match outcome: the winning and the losing teams. A Chi2 test was used to analyse the homogeneity differences between the qualitative characteristics of match episodes. The comparison between CME and NME of winner teams exhibited differences in BPDT (Chi2 (4, n=1371)= 11.880, </=. 0.01), DP (Chi2(2, n=1371)= 8.690, </=. 0.01), DT (Chi2(4, n=1371)= 15.827, </=. 0.01). Losing teams showed more generalized differences when two types of match episodes were compared. Except the OLFG, the comparison between CME and NME in loosing teams showed significant differences in all categories. Winning teams support their CME using a moderate ball pressure during defensive transition. Although with a low proportion of zone defences, results pointed out that the switching from man-to-man to a kind of zone defence could be an important reason to justify a CME. It can lead to a slight score advantage and help a team to achieve the match success.